Child–Pugh Score and Ascites for Predicting Economic Outcomes in Adult Patients with Acute Hepatitis - Teck-Jin Yang; Ting-I Lai; Wei-Che Cheng; Syi Su; Ren-Jieh Kuo; Hsiu-Po Wang; Wan-Ching Lien (Journal of Medical Ultrasound, 2014)
This study aims to determine whether clinical findings and abdominal ultrasound could be used simultaneously to predict medical resource utilization in patients of acute hepatitis. Materials and methods: A retrospective study with chart review was conducted from January 2003 to June 2007 on all patients admitted to the Emergency Department of the National Taiwan University Hospital, Taipei, Taiwan with a diagnosis of acute hepatitis. Patients with liver cirrhosis were excluded. Medical resource utilization is defined as the length of hospital stay and the total medical fee. Analysis of variance, Chi-square test, and t test were adopted in the data analysis. Results: A total of 117 patients met the inclusion criteria. The Child–Pugh score and mild ascites have positive impacts significant differences of medical on both the length of hospital stay and the total hospital charges. Our results showed a high correlation between the length of hospital stay and medical costs (r = 0.762). Conclusion: The Child–Pugh score and sonographic findings can be used to predict medical resource utilization in patients with acute hepatitis in the emergency department.